Effect of magnesium on cognition after aneurysmal subarachnoid haemorrhage in a randomized trial. (3rd September 2018) - Huenges Wajer, I. M. C.; Dorhout Mees, S. M.; van den Bergh, W. M.; Algra, A.; Visser‐Meily, J. M. A.; Rinkel, G. J. E.; van Zandvoort, M. J. E.
Abstract : Background and purpose: In randomized trials magnesium supplementation did not improve clinical outcome after aneurysmal subarachnoid haemorrhage (aSAH) on handicap scales. After aSAH, many patients have cognitive problems that may not translate into handicap. The effect of magnesium on cognitive outcome after aSAH was studied. Methods: In total, 209 patients who had been included in the Magnesium for Aneurysmal Subarachnoid Haemorrhage (MASH‐2) trial in the University Medical Centre of Utrecht were studied. Patients had been randomized to 64 mmol magnesium sulfate daily or placebo during hospitalization. Three months after aSAH patients underwent a neuropsychological examination (NPE) consisting of six neuropsychological tests or a brief cognitive assessment. Poisson and linear regression analyses were used to analyse the effect of magnesium on cognition. Results: In the magnesium group 53 (49.5%) of the 107 patients and in the placebo group 51 (50.0%) of the 102 patients scored lower than the median cognitive score [relative risk 0.99, 95% confidence interval (CI) 0.76–1.30]. Linear regression analyses showed no significant relationship between intervention and cognition ( B = 0.05, 95% CI −0.15 to 0.33). Conclusions: Treatment with magnesium has no effect on cognitive outcome after aSAH.